Participation in lifelong learning in Europe : what can be measured and compared? - Badescu, Mircea [Verfasser]; Saisana, Michaela [Verfasser] (Office for Official Publications of the European Communities, 2008)
"Comparable information and statistical measures are essential to the development and implementation of coherent and comprehensive lifelong learning strategies. Statistics and indicators already form an essential part of existing initiatives in the field of lifelong learning with a view to monitoring progress both in achieving identified targets and in implementing policy objectives. Indicators do not tell the full story but they help to identify differences, similarities and trends and to provide a starting point for further analysis in order to understand better performance and progress. This publication analyses participation patterns in lifelong learning in European countries using data provided by Eurostat from joint data collection on education Unesco-OECD-Eurostat (UOE) and from EU Labour Force Survey (LFS). Section 1 describes the European political context in the field of lifelong learning. In Section 2, indicators on participation rates in formal education (pre-primary, primary, secondary and tertiary) are discussed. Section 3 sketches upon the progress made in lifelong learning with respect to the EU benchmark. In Section 4, a simple aggregate measure of the overall participation in lifelong learning for population aged 4 to 64 in several European countries is developed and assessed. Section 5 concludes with the main aims and results of this report." (Autorenreferat, BIBB-Doku)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; S 1.5.2 Berufliche Weiterbildung; G 1.1.4 Statistiken zu speziellen Problemlagen & Bereichen; I 2.2 Europa; Lebenslanges Lernen; Berufliche Weiterbildung; Berufsbildungsstatistik; Weiterbildungsstatistik; Weiterbildungsbeteiligung; Europäische Union; Quantitative Angaben; 2000; 2005